Microcontroller based power inverter for grid connected PV system - Islam, M. M.; Rana, M. M.; Mitul, A. F.; Khan, M. M. A.; Talukder, A.; Reja, M. I.; Sarker, N.; Hoque, M. N.; Hazari, N. A. (2012 International Conference on Green and Ubiquitous Technology, 2012)
This paper represents the microcontroller based modified sine wave (MSW) generator for power inverter which is connected to the PV (Photovoltaic) system. The advantage of this inverter is the use of a low cost microcontroller that generates MSW having low harmonics and voltage regulation is fully controlled by microcontroller only which is approximately zero. It can also vary the frequency of inverter. Microcontroller ATMEGA 8L is able to store the required commands to generate the necessary MSW. In this paper how MSW signal is generated by microcontroller is reviewed. Subsequently hardware configurations of the microcontroller, algorithm, flowchart, voltage regulation and frequency control circuit using microcontroller are discussed. Finally the simulated results are shown in this paper.